Constructing novel WO3/Fe(III) nanofibers photocatalysts with enhanced visible-light-driven photocatalytic activity via interfacial charge transfer effect. (March 2017) - Ma, Ge; Chen, Zhen; Chen, Zhihong; Jin, Mingliang; Meng, Qingguo; Yuan, Mingzhe; Wang, Xin; Liu, Jun-Ming; Zhou, Guofu
Abstract: In this work, we have prepared a series of efficient visible-light-driven WO3 /Fe(III) nanofiber photocatalysts by electrospinning and impregnation method. The physical and optical properties of the prepared photocatalysts were characterized by field emission scanning electron microscope (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and the nitrogen adsorption analysis. Under the irradiation of visible light, all the prepared WO3 /Fe(III) nanofiber photocatalysts exhibit much higher activity for degrading methyl orange (MO) solution than the pristine WO3 nanofibers, and reaches 94.6% under visible light irradiation for 3 h when the relative grafting amount of Fe(III) ions was 0.003 by mass percentage. Grafting of Fe(III) ions on the surface of WO3 nanofiber could enhance its visible-light absorption and reduce the photo-generated electron-hole pairs recombination due to the interfacial charge transfer (IFCT) effect, and thus improve its photocatalytic activity, which were further verified by the ultraviolet–visible diffuse reflectance spectroscopy (UV–Vis DRS), photoluminescence (PL) and the ns-level time-resolved fluorescence decay spectrum measurements. Graphical abstract: Highlights: Visible-light-driven WO3 nanofibers photocatalyst were prepared by electrospinning method which is facile and low-cost. Photocatalytic performance was improved via rafting Fe(III) ions on the WO3 nanofiber surface due to IFCT effect. 94.6% degradation rate was achieved by WO3 /Fe(III)-0.003 under the irradiation of visible light in 180 min.